THE INFLUENCE OF PROMOTIONS AND PRICES ON PURCHASING DECISIONS AT PT. HANA ASIA TOURS KERINCI BRANCH WITH SOCIAL MEDIA AS INTERVENING VARIABLE - Regan Tisa Agachi; Emil Salim; Della Asmaria Putri (Prodi Bisnis Digital Universitas Muhammadiyah Muara Bungo, 2024)
The problem that occurred in this study was the presence of unstable sales. The purpose of this study is to identify the effect of promotion and price on purchasing decisions with social media as an intervening variable. The sample used in this study was 100 people with quantitative descriptive data analysis techniques This research is a Structural Equation Modeling (SEM) model with the Smart PLS 3.0 analysis tool. There is a significant and positive influence of promotion on purchasing decisions. There is a significant influence of price on purchasing decisions. The Company should continue to maintain promotions and economical prices and control prices to suit the economy of the community.